PENGEMBANGAN LKS BERBASIS MODEL DISCOVERY LEARNING PADA PEMBELAJARAN MATERI LENSA SISWA SMP NEGERI 4 BONTANG - WAHYUDI WAHYUDI (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2021)
This research is motivated by the existence of science teachers at SMP Negeri 4 Bontang who have not been able to make good student activity sheets (LKS) in learning. The purpose of this research is to produce discovery learning-based worksheets that are valid, practical, effective and can improve student learning outcomes. The development of worksheets in this study followed Kemp's design and was piloted in the 8th grade of SMPN 4 Bontang in the even semester of the 2013/2014 academic year. The design in this study used the One Group Pretest-Posttest Design. Collecting data using the method of observation, tests, and questionnaires. The data analysis technique used quantitative and qualitative descriptive analysis. The results of this study indicate: 1) The developed worksheets are proven to be valid, practical, and effective. The effectiveness of LKS in terms of (a) Student learning outcomes can be seen from the N-Gain with a high category, (b) Student responses to the use of LKS are very positive. It was concluded that the LKS based on the discovery learning model that was developed was valid, practical and effective to improve learning outcomes. ABSTRAKPenelitian ini dilatarbelakangi oleh keberadaan guru IPA SMP negeri 4 Bontang yang belum mampu membuat lembar kegiatan siswa (LKS) yang baik dalam pembelajaran. Tujuan penelitian ini adalah untuk menghasilkan LKS berbasis discovery learning yang valid, praktis, efektif dan dapat meningkatkan hasil belajar siswa. Pengembangan LKS dalam penelitian ini mengikuti desain Kemp dan diujicobakan di kelas 8 SMPN 4 Bontang semester genap tahun ajaran 2013/2014. Desain dalam penelitian ini menggunakan One Group Pretest-Posttest Design. Pengumpulan data menggunakan metode observasi, tes, dan angket. Teknik analisis data menggunakan analisis deskriptif kuantitatif, dan kualitatif. Hasil penelitian ini menunjukkan: 1) LKS yang dikembangkan terbukti valid, praktis, dan efektif. Kefektifan LKS ditinjau dari (a) Hasil belajar siswa terlihat dari N-Gain dengan kategori tinggi, (b) Respon siswa terhadap penggunaan LKS sangat positif. Disimpulkan bahwa LKS berbasis model discovery learning yang dikembangkan valid, praktis dan efektif untuk meningkatkan hasil belajar.